2019
DOI: 10.21307/joss-2019-008
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Contextual Patterns in Family Health History Knowledge among African American Adults: A Mixed-Methods Social Network Analysis Study*

Abstract: Background: Family health history is a strong risk factor for many chronic diseases. Ethnic minorities have been found to have a low awareness of their family health history (FHH), which may pose a contributing factor to health disparities. Purpose: The purpose of this mixed-methods social network analysis study was to identify structural and contextual patterns in African American adults' FHH knowledge based on interpersonal communication exchanges with their family members. Methods: African American adults c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Qualitative and mixed-methods research has found that compared to white Americans, African Americans may communicate less with their family members about FHH [26,27] and that diverse patterns of communication about FHH within African American families are impacted by family member characteristics and relationship quality [28,29]. Overall, more research is needed to understand the acceptability and effectiveness of FHH to change behavior among low-income, African American families and to understand how interventions can be tailored to family structures and systems.…”
Section: Evaluation Of Fhh Interventions Among Low-income African Americansmentioning
confidence: 99%
“…Qualitative and mixed-methods research has found that compared to white Americans, African Americans may communicate less with their family members about FHH [26,27] and that diverse patterns of communication about FHH within African American families are impacted by family member characteristics and relationship quality [28,29]. Overall, more research is needed to understand the acceptability and effectiveness of FHH to change behavior among low-income, African American families and to understand how interventions can be tailored to family structures and systems.…”
Section: Evaluation Of Fhh Interventions Among Low-income African Americansmentioning
confidence: 99%
“…The opinions expressed by authors contributing to this journal do not necessarily reflect the opinions of the U.S. Department of Health and Human Services, the Public Health Service, the Centers for Disease Control and Prevention, or the authors' affiliated institutions. ences in FCH communication (6,8). Thus, a potential limitation of this study is that the HINTS survey did not capture diverse conceptualizations of "family" that may include nonbiological relatives who nonetheless engage in FCH discussions (eg, spouses, inlaws, godparents).…”
Section: November 2020mentioning
confidence: 99%
“…To this end, digital tools, such as the US Surgeon General's My Family Health Portrait, could be promoted to support tracking of family health history (29)(30)(31). However, effective use of family cancer histories will entail supporting communication among individuals, families, and health care providers as well as health care systems-level support for systematic FCH collection and clinical decision making (8,17,26). Continued surveillance of FCH communication behavior is recommended as personalized medicine advances and access to genetic testing expands among the population.…”
Section: November 2020mentioning
confidence: 99%
See 1 more Smart Citation